Frailty and mortality among older patients in a tertiary hospital in Nigeria. (2019)
Background: This study determined the frailty status and its association with mortality among older patients. Design: A prospective cohort design. Setting: Study was conducted at the medical wards of University College Hospital, Ibadan, Nigeria. Participants and study tools: Four hundred and fifty older patients (>60 years) were followed up from the day of admission to death or discharge. Information obtained includes socio demographic characteristics and clinical frailty was assessed using the Canadian Study of Health and Aging (CSHA) scale. Bivariate and multivariate analyses were carried out using SPSS version 21 at a p <0.05. Results: Overall, frailty was identified in 285 (63.3%) respondents. Mortality was significantly higher among frail respondents (25.3%) than non-frail respondents (15.4%) p=0.028. Logistic regression analysis showed factors associated with frailty were: male sex (OR=1.946 [1.005–3.774], p=0.048), non-engagement in occupational activities (OR=2.642 [1.394–5.008], p=0.003), multiple morbidities (OR=4.411 [1.944–10.006], p<0.0001), functional disability (OR=2.114 [1.029–4.343), p=0.042], malnutrition (OR=9.258 [1.029–83.301], p=0.047) and being underweight (OR=7.462 [1.499–37.037], p=0.014). Conclusion: The prevalence of frailty among medical in-hospital older patients is very high and calls for its prompt identification and management to improve their survival.